Double mimicry evades tRNA synthetase editing by toxic vegetable-sourced non-proteinogenic amino acid - Youngzee Song (Nature Portfolio, 2017)
Non-proteinogenic (np) amino acids in the food chain present challenges for the human translation machinery. Here the authors show that, while AlaRS and ProRS activate toxic np azetidine-2-carboxylic acid (Aze) present in sugar beets and lilies, only the AlaRS editing system rejects Aze.